Mechanical characterization of visually claáified, small-diameter laricio pine timber - Fernandez Golfin, J.I.=700 1 Diez Barra, M.R.; Hermoso, E.; Mier, R.
(En, Es)
Ilus., 22 ref.
Keywords: PINUS NIGRA; MADERA EN ROLLO; EVALUACION; ESPAÑA